UPAYA INDONESIA DALAM MEWUJUDKAN VISI POROS MARITIM DUNIA MELALUI ASEAN OUTLOOK ON THE INDO-PASIFIC (AOIP) - Ayunda Wimanora; Hendrini Renolafitri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Indonesia's efforts in realizing the vision of the World Maritime Fulcrum are considered successful in terms of the various activities and cooperation carried out by Indonesia through AOIP. Based on this success, this research wants to analyze how Indonesia's efforts are in realizing the vision of the World Maritime Axis through the ASEAN Outlook on The Indo-Pacific (AOIP). To answer research questions, this study uses 5 component indicators in the theory of Regionalism by Welter S. Jones which are guided by: 1) Maximizing economic potential; 2) Maximizing political potential; 3) Settlement of regional conflicts. The results of this study prove that the success of Indonesia's efforts in realizing the vision of the World Maritime Axis through AOIP is determined by 3 components of regionalism theory, namely: 1) Maximizing economic potential by giving priority to infrastructure development and maritime connectivity with ASEAN dialogue partner countries, 2) Maximizing political potential, namely efforts through Maritime Diplomacy in overcoming issues of maritime shipping and technical cooperation in marine science through collaboration between the public and the private sector in the region 3) Regional Conflict Resolution, namely through offering increased cooperation in the maritime field and efforts to deal with sources of conflict, such as theft fish, ownership violations, territorial disputes, piracy, and marine pollution with an emphasis that the sea must be free from various nations and not separate; Building maritime strength as a responsibility to maintain shipping safety and Maritime Security. Keywords: AOIP, World Maritime Axis, Maritime Diplomacy